ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) IN THE CITY OF PEKANBARU - Zahra Aulia Putri (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The formation of ETLE is a technological development carried out from manual (Conventional) tickets to electronic tickets (ETLE) to prevent traffic accidents and accidents. This study aims to find an analysis of the implementation of Electronic Traffic Law Enforcement (ETLE) in the city of Pekanbaru and what are the obstacles to the implementation of Electronic Traffic Law Enforcement (ETLE) in the city of Pekanbaru. This research method uses a qualitative descriptive method with the collection of interviews, observations, and documentation data. This research uses Edward's theory with the indicators used, namely: Communication, Resources, Disposition, and Bureaucratic Structure. The results of this study show that the implementation of Electronic Traffic Law Enforcement (ETLE) in the city of Pekanbaru has been carried out well and as it should, but there are several obstacles such as less optimal communication between the police and the community regarding ETLE, limited ETLE facilities in arresting traffic violators, and cultural factors of the community who are afraid of being violated if there is a police guard.